Proceedings of 2010 International Symposium on VLSI Design, Automation and Test 2010
DOI: 10.1109/vdat.2010.5496677
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical stress characterization of tungsten-fill through-silicon-via

Abstract: Thermo-mechanical stress of tungsten-filled (W-fill) through-silicon-via (TSV) is strongly depending on via shape, size and inter-via spacing, which places constraints on TSV design, including 2-D integrated circuit layout and 3-D structure profile. This paper summarizes these constraints and co-relations among thick (up to 1.2μm) tungsten (W) film, W-fill TSV, and surrounding silicon structures, using Flexus bowing measurement, Wright etch method, and also 3-D TSV stress simulations. In this study, the stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…As-deposited W exhibits large compressive stresses on the substrate [111], which increase with an increasing TSV diameter and decreasing TSV pitch. Unfortunately annealing at 400°C does not significantly relieve the stress [110].…”
Section: B Sidewall Insulationmentioning
confidence: 99%
“…As-deposited W exhibits large compressive stresses on the substrate [111], which increase with an increasing TSV diameter and decreasing TSV pitch. Unfortunately annealing at 400°C does not significantly relieve the stress [110].…”
Section: B Sidewall Insulationmentioning
confidence: 99%
“…Via-middle TSVs require a relatively large (12:1 or higher) aspect ratio [14][15][16]20]. Thus, the width of via-middle TSVs is comparable to the width of via-first TSVs whereas the height is comparable to via-last TSVs.…”
Section: Via-middle Tsvmentioning
confidence: 99%
“…For example, in [12] and [29], via-first TSV technology has been investigated with little attention on circuit design implications. Similarly, via-middle TSVs have been discussed in [14][15][16] focusing primarily on process characteristics. The fabrication constraints of the three TSV technologies are also compared in [30].…”
Section: Previous Workmentioning
confidence: 99%
“…To reduce the Cu-filling time, a pulse-reverse (PR) current waveform (modified from the pulse current) 11,12) or the addition of inhibitors and accelerators to the plating solution have been reported. 13) As a fundamental solution to overcome these problems, several recent studies have looked into replacing copper with different filling materials, such as tungsten, 14) polymers, 15) alloys, 16) and solders, 17) in an attempt to reduce the thermomechanical stress and shorten the Cu-filling time. He et al 18) suggested a Cu-cored solder for rapid and low-cost processing for TSV fabrication.…”
Section: Introductionmentioning
confidence: 99%